2022
DOI: 10.3390/ijerph20010700
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Cervical Screening Adoption among Female University Students Based on the Precaution Adoption Process Model and Health-Belief Model

Abstract: This study aimed to identify the decisional stages for cervical screening and corresponding cognitive factors in female university students. A cross-sectional study was conducted among Korean female university students aged 20–29 years through an online survey. The main outcome was the decisional stage of cervical screening adoption using the precaution adoption process model. The stages were classified into pre-adoption (the unawareness, unengaged, and undecided stages), adoption (the decided to act and actin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…3,[20][21][22] Of the included 21 studies, only 1 study reported on all HBM constructs, 10 while 8 reported on at least the 4 primary constructs. 3,4,8,10,16,19,20,23 Figure 2 showcases the distribution of publications over time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…3,[20][21][22] Of the included 21 studies, only 1 study reported on all HBM constructs, 10 while 8 reported on at least the 4 primary constructs. 3,4,8,10,16,19,20,23 Figure 2 showcases the distribution of publications over time.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, no studies originated from the Middle East and North Africa (MENA) region. The earliest studies were published in 2007 and the latest were circulated during 2022 4,16,17 . The studies included a total of 15,365 participants with studies contributing at least 171 participants to a maximum of 3249 participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations